FUNDAMENTALIZATION OF ICT LEARNING IN MODERN HIGH TECH ENVIRONMENT - Shyshkina М.П.; Kogut У.П. (Journal of Information Technologies in Education (ITE), 2014)
The article outlines the features of the process of fundamentalization of ICT learning,educational background to ensure it in high school. The concept of fundamental knowledge and its role in training of a specialist is described. The problems of access to qualitative education,particularly to electronic learning resources in modern high-tech environment are revealed. The role of computer mathematics as a tool of ICT learning fundamentalization is emphasized.